Extensive hydrogen supersaturations in the western South Atlantic Ocean suggest substantial underestimation of nitrogen fixation. Issue 7 (16th July 2014) - Moore, Robert M.; Kienast, Markus; Fraser, Michael; Cullen, John J.; Deutsch, Curtis; Dutkiewicz, Stephanie; Follows, Michael J.; Somes, Christopher J.
Abstract The nitrogen cycle is fundamental to Earth's biogeochemistry. Yet major uncertainties of quantification remain, particularly regarding the global oceanic nitrogen fixation rate. Hydrogen is produced during nitrogen fixation and will become supersaturated in surface waters if there is net release from diazotrophs. Ocean surveys of hydrogen supersaturation thus have the potential to illustrate the spatial and temporal distribution of nitrogen fixation and to guide the far more onerous but quantitative methods for measuring it. Here we present the first transect of high resolution measurements of hydrogen supersaturations in surface waters along a meridional 10, 000 km cruise track through the Atlantic. We compare measured saturations with published measurements of nitrogen fixation rates and also with model‐derived values. If the primary source of excess hydrogen is nitrogen fixation and has a hydrogen release ratio similar to Trichodesmium, our hydrogen measurements would point to similar rates of fixation in the North and South Atlantic, roughly consistent with modeled fixation rates but not with measured rates, which are lower in the south. Possible explanations would include any substantial nitrogen fixation by newly discovered diazotrophs, particularly any having a hydrogen release ratio similar to or exceeding that of Trichodesmium; undersampling of nitrogen fixation south of the equator related to excessive focus on Trichodesmium; and methodological shortcomings of nitrogen fixation techniques that cause a bias toward colonial diazotrophs relative to unicellular forms. Alternatively, our data are affected by an unknown hydrogen source that is greater in the southern half of the cruise track than the northern.